The Armed Conflict in Ukraine: Use of Force, Prosecution, and Complicity - Mizalfia Nursabrina (Padjadjaran Journal of International Law, 2022)
In the early hours of Thursday, 24 February 2022, President Vladimir Putin addressed the Russian people and declared to the world that Russia has decided to commence a “special military operation” against Ukraine. Shortly afterwards, the Russian military entered Ukrainian territory from many parts of the country. The conflict has resulted in heavy casualties, especially within the Ukrainians. The international community has condemned the invasion, stating that it violates Ukraine’s territorial integrity and sovereignty, and it’s contrary to the principles embodied in the Charter of the United Nations (UN Charter). The North Atlantic Council has also identified the attack as “a grave violation of international law, including the UN Charter. In the wake of protests sounded by the international community, Russia has continued to oppose such arguments. As a preliminary analysis, it is evident that Russia’s actions against Ukraine consist of elements of force. Rather than denying the allegations, Russia has justified its use of force by referring to principles of international law. This paper examines a brief background of the Russo-Ukrainian conflict, Russia’s and Ukraine’s justifications in the war, the possible prosecution of high-ranking Russian officials in potential fora’s, and also Belarus’ involvement in the conflict. While this paper finds that Russia’s justifications for their invasion are unlawful and invokes their responsibility, there are obstacles in prosecuting the crimes. It also considers that Belarus is responsible for their involvement.